Hands-on guide to creating Flash advertising : from concept to tracking--microsites, video ads, and more - Fincanon, Jason (Focal hands-on guide series., 2008)
Create awe-inspiring, mind-blowing Flash ads and microsites that engage consumers and demonstrate their worth to clients. The Hands-On Guide to Creating Flash Advertising delivers the nuts and bolts of the development process from initial design conception to ad completion. You'll learn the best practices for:* Mastering the myriad of ad specs, deadlines, quality and version control issues* Creating ads that balance campaign goals with design constraints* Preparing and building ads with team and QC standards* Using.